GOVERNMENT COLLABORATION MODEL IN DISASTER MANAGEMENT IN PONOROGO REGENCY - Khoirurrosyidin Khoirurrosyidin; Yusuf Adam Hilman; Bambang Widiyahseno; Edi Kurniawan; Seventeena Agustin Veby Kartika Putri (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
Disaster management must be carried out in a structured manner, involving many parties or stakeholders, so that the government cannot be the sole actor. The problem formulation in this study is how to implement an effective government collaboration model. The objective of this study is to find the most ideal model of collaboration in disaster management in Ponorogo Regency. This study uses a descriptive qualitative method. The results of the study show that the practice of Collaborative Governance is key to the process of resolving disaster issues in Ponorogo. as seen from various collaborations that demonstrate the complexity of the actors involved, resulting in faster recovery and normalisation of community life after a disaster. In addition, the intensity of coordination and communication is an absolute requirement in the process of resolving disaster events. It should be remembered that prevention is paramount in disaster management, so prevention efforts need to be optimised. In this study, we have limitations, one of which is that the disaster management model is sometimes ineffective due to the involvement of many actors with different interests, which hinders the resolution of disaster events. Therefore, it is necessary to examine the roles of each actor in more depth.